Hyperpolarized (13)C Spectroscopy with Simple Slice-and-Frequency-Selective Excitation - Topping, Geoffrey J. (Biomedicines, 2021)
Hyperpolarized (13)C nuclear magnetic resonance spectroscopy can characterize in vivo tissue metabolism, including preclinical models of cancer and inflammatory disease. Broad bandwidth radiofrequency excitation is often paired with free induction decay readout for spectral separation, but quantification of low-signal downstream metabolites using this method can be impeded by spectral peak overlap or when frequency separation of the detected peaks exceeds the excitation bandwidth. In this work, alternating frequency narrow bandwidth (250 Hz) slice-selective excitation was used for (13)C spectroscopy at 7 T in a subcutaneous xenograft rat model of human pancreatic cancer (PSN1) to improve quantification while measuring the dynamics of injected hyperpolarized [1-(13)C]lactate and its metabolite [1-(13)C]pyruvate. This method does not require sophisticated pulse sequences or specialized radiofrequency and gradient pulses, but rather uses nominally spatially offset slices to produce alternating frequency excitation with simpler slice-selective radiofrequency pulses. Additionally, point-resolved spectroscopy was used to calibrate the (13)C frequency from the thermal proton signal in the target region. This excitation scheme isolates the small [1-(13)C]pyruvate peak from the similar-magnitude tail of the much larger injected [1-(13)C]lactate peak, facilitates quantification of the [1-(13)C]pyruvate signal, simplifies data processing, and could be employed for other substrates and preclinical models.